Belian Sasak as a life practice: The concept of sickness–health and the cosmology of healing - Sibawaihi, Muhammad; Lailaturrahmah, Etika (Universitas Muhammadiyah Malang, 2026)
Every society develops its own understanding of the body, illness, and healing, shaped by historical, cosmological, social, and cultural constructions that are experienced and transmitted across generations. Within the biomedical paradigm, illness is understood as a dysfunction of bodily organs, whereas in traditional societies it is interpreted as social imbalance, moral transgression, or spiritual disturbance. Departing from this ontological divergence, this study examines how the healing practices of the Belian Sasak in Lombok construct, articulate, and reaffirm the realities of illness and healing. This study adopts a qualitative research approach grounded in ethnography and supported by a review of relevant literature. Data were collected through participant observation and in-depth interviews, and were analyzed using narrative analysis of ritual healing practices. The findings reveal that the belian functions as an ontological actor who, through ritual acts, speech, and symbolic mediation, reactivates and sustains the local cosmology. The efficacy of healing does not rest solely on individual intention, but on the repetition of socially recognized practices that shape a shared horizon of belief. Healing within the Belian practice thus constitutes a relational event that reorders the relationships among the body, community, nature, ancestors, and God.These findings suggest that traditional medicine cannot be reduced merely to a therapeutic technique; rather, it must be understood as a practice that produces and stabilizes the social reality of healing itself. This study contributes to the development of the ontology of medicine and expands our understanding of how healing practices operate within the local cosmology of the Sasak community. Setiap masyarakat memiliki cara pandang sendiri tentang tubuh, penyakit, dan penyembuhan yang terbentuk dari konstruksi historis, kosmologis, sosial, dan kultural yang mereka alami dan warisi. Dalam masyarakat biomedis, sakit dianggap sebagai gangguan fungsi organ, sementara dalam masyarakat tradisional sakit dimaknai sebagai ketidakseimbangan sosial, pelanggaran moral, atau gangguan spiritual. Berangkat dari perbedaan ontologis tersebut, penelitian ini mengkaji bagaimana praktik belian Sasak di Lombok membentuk, mengartikulasikan, dan meneguhkan realitas sakit dan kesembuhan. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi, melalui observasi partisipan, wawancara mendalam, dan analisis naratif atas praktik ritual penyembuhan. Hasil penelitian menunjukkan bahwa belian berperan sebagai aktor ontologis yang melalui ritual, tutur, dan simbol mengaktifkan kembali kosmologi lokal. Daya kerja penyembuhan tidak terletak semata pada intensi individu, melainkan pada pengulangan praktik yang diakui secara sosial dan membentuk horizon keyakinan kolektif. Dengan demikian, kesembuhan dalam praktik belian merupakan peristiwa relasional yang menata ulang hubungan antara tubuh, komunitas, alam, leluhur, dan Tuhan. Temuan ini menunjukkan bahwa pengobatan tradisional tidak dapat direduksi menjadi teknik terapeutik saja, melainkan harus dipahami sebagai praktik yang memproduksi dan menstabilkan realitas sosial tentang pengobatan itu sendiri. Penelitian ini berkontribusi pada pengembangan kajian ontologi pengobatan dan memperluas pemahaman tentang bagaimana praktik penyembuhan bekerja dalam konteks kosmologi lokal masyarakat Sasak.